Wybrane problemy mieszkańców Nowej Huty na podstawie listów do „Głosu Nowej Huty” z lat 1956–1970 - Chłosta-Sikorska, Agnieszka (Res Gestae. Czasopismo historyczne, 2023)
In 1949, the communist rulers of Poland decided to build Nowa Huta, the steelworks and city near Kraków. According to the propaganda, it was supposed to be the first model socialist city in Poland. Residents were to experience social promotion, comfortable apartments, cultural institutions, and rest in their home space. In addition to housing, well-stocked shops, high -quality services, assistance in daily activities such as food preparation, health care and childcare were offered. However, the reality differed from this propaganda vision. In the local press such as the weekly Budujemy Socjalizm, later transformed into Głos Nowej Huty, letters to the editorial office complained about housing problems, insufficient supplies, queues, difficulties in organizing holidays, or low quality of the cultural offer. Letters to the editor are an important source for research on the everyday life of the Polish People’s Republic. They reflected the small and big problems of the inhabitants seeking help from journalists, believing that the press had substantial influence on the ruling class.